Treatment of ventricular fibrillation in the dog improved demonstration methodology to present clinical rationale - Sims, Michael H., 1944-; University of Tennessee, Knoxville. College of Veterinary Medicine (Knoxville : College of Veterinary Medicine, University of Tennessee, 1980)
Purpose is to present set up instructions, introduction and calibration procedures for the demonstration concerning the treatment of ventricular fibrillation in the dog.
Keywords: Ventricular fibrillation; Dogs -- Diseases